Modernization the Cinema Medium through Visual Transformation of NOAH’s Album Remake Version - Teddy Afriansyah; Meyrasyawati, Dewi; Dwi Riyanto, Edi (Universitas Negeri Semarang, 2025)
This research discusses how NOAH gave a modern change (modernization) sentiment in video clips, so it can be enjoyable by fans of NOAH. The objectives are, 1) Explain the visual modernization change in NOAH’s video clips remake version; and 2) Explain the visual modernization that is able to reconstruct NOAH's identity. This research uses a qualitative method with a musicological approach. The research data was collected through virtual observation from video clips of NOAH’s remake music video. This research showed that 1) a visual comparison was conducted across six NOAH music videos comparing original and remake versions, such as